The Influence of The Problem Based Learning Model on Learning Outcomes of Class V Students in Science Learning at UPTD SDN 125543 Pematang Siantar T.A 2023/2024 - Nanci H. Lumbanraja; Lisbet Novianti Sihombing; Canni Loren Sianturi (International Journal of Integrated Science and Technology, 2023)
This research aims to determine whether there is an influence of the problem based learning model on the learning outcomes of class V students in science learning at UPTD SD Negeri 125543 Pematang Siantar FY 2023/2024, the method in this research is a quantitative experimental type method whose research design is pre-experimental. one group pretest-posttest type. Conducted in September 2023, the population of all students at UPTD SD Negeri 125543 Pematang Siantar and a sample of 22 students consisting of 14 female students and 8 male students were used, namely two research variables: the dependent variable (x) the influence of the learning model problem based learning (y) student learning outcomes , the concept of learning is a result of achievement in teaching and learning activities which is achieved through a learning process which can be measured by the student's achievement or ability to achieve. Data collection techniques are test techniques with validity tests, reliability tests, difficulty level tests, and distinguishing power tests. The test results using the N-gain technique with the help of the SPSS version 21 program, based on the calculation results obtained a mean of 0.5588, with an effectiveness of 0.7>0.5588>0.3 which is in the medium category, in the ANOVA test the significance value was 0.002, which is where category 0.002<0.05 then HO is rejected Ha is accepted. This means that all independent variables have a significant influence on learning outcomes and have a significant influence on the dependent variable. So it can be concluded that there is an influence of the problem based learning model on the learning outcomes of class V students at UPTD SD Negeri 125543 Pematang Siantar FY 2023/2024.